STRATEGI YANDERE DALAM MENYAMPAIKAN PERASAAN PADA FILM AKU NO HANA - Ariana, Rani Wulansari; Anggi Septiandi (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
Title of this research is Strategy of Yandere Character’s Love Confession in Aku no Hana. This research objective is to know the strategy of the yandere in conveying feelings for her loved ones. It is known that strategy of yandere love confession on Aku no Hana was done in a gradual way like obsessive, manipulative and force action to coercion on her romantics opponent, there’s possibility on the next action can result in acts of violance. The yandere in this movie makes his romantic opponents in such a way that the nature of dependence is formed. The actions performed have intention to attract attention and the way this character expresses her feelings to the person she loves. and this research. the research of analysis are from obsession type until double self suicide type. and for sociolinguistics analysis is directive narrative and expression narrative.